The History Of The Battle Of Khandaq: A Study Of The Value Of Leadership And Its Contribution To The Study Of Islamic HistoryThe History Of The Battle Of Khandaq: A Study Of The Value Of Leadership And Its Contribution To The Study Of Islamic History - Wiwaha, Rizzaldy Satria; Syawali, Cecep Helmi; Nasrulloh, Emil; Hirji, Taufik; Muthmainnah, Muthmainnah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this study is to find out the reasons why leadership determines victory in the Khandaq War, the values of leadership in the Khandaq War, and the contribution of leadership values in the Khandaq War in 627 AD with Islamic History teaching materials. This research is historical research. Sources of data used are primary sources and secondary sources. The main source in this research is the Al-Qur'an. Secondary sources in this study are hadiths and books that are relevant to the subject of research. Data collection in this study was collected using library research techniques and documentation techniques. Data analysis in this study used historical analysis, descriptive analysis and content analysis. The stages of the research procedure consist of heuristics, criticism (both internal and external), interpretation, and historiography. The results showed that the Battle of Khandaq was one of the wars won by the Muslims because the Prophet as a military leader was able to deal with changes in the war situation quickly and precisely. Then, there are leadership values in the Khandaq War consisting of the values of God, trust and responsibility, justice, firmness, and visionary. In addition, this historical event has relevance to Islamic history teaching materials, especially material about the existence of Islam during the time of the Prophet Muhammad in Medina.